Effect of Theraband Exercise on Knee Pain Reduction in Osteoarthritis Patients - Dela Ramona; Wahyu Tri Sudaryanto (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Osteoarthritis (OA) is a degenerative joint disease associated with damage to joint cartilage, where a complex joint degradation process occurs, consisting of a repair process in the cartilage, bone, and synovium, followed by a secondary component of the inflammatory process. The primary cause of osteoarthritis is still not known for certain, but there are several risk factors that play a role, namely: age, gender, genetics, obesity, metabolic diseases, and other factors. This study aimed to examine the effect of theraband exercise on reducing knee pain in OA patients. Subjects and Method: This was a quasy experiment study conducted at Dr. Soedjono Hospital, in Magelang, Central Java, from May to June 2023. A sample of 33 knee osteoarthritis patients was selected using purposive sampling. Intervention group (n= 17) received Theraband exercise and control group (n= 16) received usual care. The dependent variable was knee pain. The independent variable was Theraband exercise. Knee pain was measured using a visual analogue scale (VAS). The data were tested using independent t test. Results: After intervention, mean of VAS score in the intervention group (Mean= 5.25; SD= 1.57) was slightly higher than control group (Mean= 5.13; SD= 1.75), but it was statistically non-significant (p= 0.848). Conclusion: Mean of VAS score in the intervention group is slightly higher than control group, but it is statistically non-significant. Keywords: theraband exercise, pain, osteoarthritis knee. Correspondence: Dela Ramona. Study Program of Physiotherapy, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. Jl. A. Yani Kartasura, Sukoharjo, Central Java, 57162 Email: delaramona26@gmail.com. Mobile: +6281347988116.